Інноваційні процеси творення аксіологійних значень в українській лінгвокультурі: проєкція на антропоніми та їхні похід - Kovtun, Oksana (Theoria et Historia Scientiarum, 2024)
Some changes connected with sociolinguistic factors, in particular, the Russian-Ukrainian war, that are taking place in the Ukrainian vocabulary are characterized. The trends of rethinking anthroponyms and their derivatives, which, thanks to the linguistic creativity of Ukrainians, are widespread in modern Ukrainian media discourse and recorded in dictionaries of new words and meanings, as carriers of evaluatively marked meanings and senses, are highlighted. The lexical structure of the Ukrainian language is being updated on the basis of the innovative word formation processes system.